Kemas Ulang Informasi tentang Penyakit Kaki Gajah (FILARIASIS) - Desra, Silvia Fitri Yuli (Ilmu Informasi Perpustakaan dan Kearsipan, 2017)
The purpose of this paper is to 1) find out an overview of elephant foot disease in Agam. 2) Describe the Information on Elephant Foot Disease (Filariasis). The method that is used a descriptive method, and the data collecting technique throught direct literature study is data collection using books, articles online and printed. Based on analyzing the data, it is concluded: (1) 18 people in Agam Regency have elephantiasis disease, 18 residents are spread in Lubuk Basung, Tanjung Mutiara, Palembayan, AmpekÂ Nagari and others. Elephant foot with leg condition has been enlarged and difficult to be cured. Previously, there were 46 people who suffered from elephantiasis and died as many as 28 people; (2) the steps in making about the re-packing of information about elephantiasis (filariasis) are as follows: (a) topic determination; (b) tracking information in accordance with predetermined topics; (c) processing information, evaluating and tracing information; (d) determine the form of information packaging and packing of information; (e) disseminating information by means of promotion.Keyword: Agam, filariasis, repackaging information.